Orbit-Stabilizer Theorem (with proof)

Orbit-Stabilizer Theorem

Let G be a group which acts on a finite set X. Then \displaystyle |\text{Orb}(x)|=[G:\text{Stab}(x)]=\frac{|G|}{|\text{Stab}(x)|}.


Define \phi:G/\text{Stab}(x)\to\text{Orb}(x) by \displaystyle \phi(g\text{Stab}(x))=g\cdot x.


Note that \text{Stab}(x) is a subgroup of G. If g\text{Stab}(x)=h\text{Stab}(x), then g^{-1}h\in\text{Stab}(x). Thus g^{-1}hx=x, which implies hx=gx, thus \phi is well-defined.


\phi is clearly surjective.


If \phi(g\text{Stab}(x))=\phi(h\text{Stab}(x)), then gx=hx. Thus g^{-1}hx=x, so g^{-1}h\in\text{Stab}(x). Thus g\text{Stab}(x)=h\text{Stab}(x).

By Lagrange’s Theorem, \displaystyle \frac{|G|}{|\text{Stab}(x)|}=|G/\text{Stab}(x)|=|\text{Orb}(x)|.

Field Medallist Prof. Gowers has also written a nice post on the Orbit -Stabilizer Theorem and various proofs.


Author: mathtuition88

Math and Education Blog

One thought on “Orbit-Stabilizer Theorem (with proof)”

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out /  Change )

Twitter picture

You are commenting using your Twitter account. Log Out /  Change )

Facebook photo

You are commenting using your Facebook account. Log Out /  Change )

Connecting to %s

This site uses Akismet to reduce spam. Learn how your comment data is processed.

%d bloggers like this: